2019
DOI: 10.1016/j.envpol.2018.11.043
|View full text |Cite
|
Sign up to set email alerts
|

Environmental responsibility for sulfur dioxide emissions and associated biodiversity loss across Chinese provinces

Abstract: Recent years have witnessed a growing volume in Chinese interregional trade, along with the increasing disparities in environmental pressures. This has prompted an increased attention on where the responsibilities for environmental impacts should be placed. In this paper, we quantify the environmental responsibility of SO 2 emissions and biodiversity impacts due to terrestrial acidification at the provincial level for the first time. We examine the environmental responsibility from the perspectives of producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 62 publications
2
36
0
Order By: Relevance
“…The embodied interprovincial material transfer within China is almost equal to the total MF of the United States (at 9.8 Gt [https://www.resourcepanel.org/global-material-flows-database]). On a provincial level, we find similar MF patterns as those between countries at the global scale (710) and provincial-level footprint studies for carbon, PM2.5, and SO 2 (1115): material demands in affluent areas are supported by extraction and production in less-developed areas. There are 12 provinces, located mainly along the coasts, which are net national and international MF importers (Fig.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…The embodied interprovincial material transfer within China is almost equal to the total MF of the United States (at 9.8 Gt [https://www.resourcepanel.org/global-material-flows-database]). On a provincial level, we find similar MF patterns as those between countries at the global scale (710) and provincial-level footprint studies for carbon, PM2.5, and SO 2 (1115): material demands in affluent areas are supported by extraction and production in less-developed areas. There are 12 provinces, located mainly along the coasts, which are net national and international MF importers (Fig.…”
Section: Resultssupporting
confidence: 73%
“…Material outsourcing patterns also show large material leakages as the virtual flow almost always runs from regions with a high material intensity to areas with a low intensity (compare Figs. 2 B and 3) (12, 13).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This insight has led to proposals for mixed approaches in which some form of responsibility sharing is suggested. Rodrigues et al (2006) and Qian, Behrens, Tukker, Rodrigues, and Scherer (2019) use the average of consumption-based and income-based emissions. Kander et al (2015) propose a 'technologically corrected' consumption-based approach.…”
Section: Nomentioning
confidence: 99%
“…The results suggested that high demand is the main factor contributing to sulfur dioxide emissions in energy supply. Qian et al [17] pointed out that developed provinces needed to undertake enormous environmental responsibility, which led to the fact that they mainly outsourced their sulfur dioxide emissions to nearby developing provinces. Taking sulfur dioxide emissions as an example, Wang et al [18] explored the pollution haven hypothesis in domestic trade for the first time, and found that little evidence supported that this phenomenon existed in China over 2007–2012.…”
Section: Introductionmentioning
confidence: 99%